Edukasi Gizi Seimbang pada Remaja di Pondok Pesantren As’ad Kota Jambi - Wulansari, Arnati; Rahmawati, Helfi (Universitas Baiturrahim, 2025)
Currently, health programs have not touched on the Islamic boarding school education segment. Most of the activities in Islamic boarding schools involve studying and the activities are regularly scheduled. One of the Islamic boarding schools is the As'ad Islamic Boarding School, where this boarding school is one of the oldest Islamic boarding schools and the number of students per year is quite large. This activity aims to provide education about balanced nutrition for teenagers. The activity was attended by 28 audience members who were young women. Activities will be carried out from September 2023 to January 2024 at the As'ad Islamic Boarding School, Jambi City. This activity was carried out using the discussion method. The results of community service showed that as many as 21% of the audience had good knowledge in the pretest. The posttest results increased with the good knowledge category amounting to 79%. In the discussion session, many questions were asked related to balanced nutrition and most of them also shared their experiences regarding balanced nutrition. It can be concluded that after carrying out this activity, the audience can understand about balanced nutrition.